The coping strategies of athletes returning to sports after anterior cruciate ligament reconstruction - Aljecera, Erica Ann G. 2001-
Anterior Cruciate Ligament Reconstruction (ACLR) is a procedure that restores the stability of a torn Anterior Cruciate Ligament (ACL). ACLR requires a long-term recovery which causes major setbacks for the athletes that affect their mental stability. Physical readiness needs to be combined with psychological readiness. The objective of the study is to identify the different types of coping strategies that were used by the athletes and to determine the coping strategy that made the athletes return to their respective sports again. Ten participants answered the Brief Coping Orientation to Problems Experienced (Brief-COPE) questionnaire, and an open-ended, one-on-one interview was conducted with the six participants. The data was analyzed using descriptive statistics and thematic analysis to identify the coping strategy and determine the different coping strategies of the athletes that made them return to sports. The study shows that problem-focused coping is the most used coping strategy. From the respondents’ responses, three themes were derived (Positive coping to play again, Low Self-Esteem, The Effects of Emotional Support, and Pushing Themselves and Gaining Confidence.) Increasing the number of participants and using different tools are recommended for future studies